Inquiring Minds Want to Know: Do Justices Tip Their Hands with Questions at Oral Argument in the U.S. Supreme Court? - Timothy R. Johnson; Ryan C. Black; Jerry Goldman; Sarah A. Treul (Washington University Journal of Law & Policy, 2009)
Part I of this Essay focuses on what Justices and scholars have written and said about oral arguments generally and the role these proceedings play in the Court’s decision-making process. Part II examines the few existing studies that address the question posed here. Part III lays out the data used to test this hypothesis; Part IV presents the methodology; and Part V discusses the results.
Keywords: Judicial process; Forensic oratory; U.S. Supreme Court; Empirical analysis; Judicial decision-making